O conceito de episteme em Platão: análises em diálogos do período intermediário ao da maturidade - Ramos Filho, José Silva (2016)
This dissertation focuses on the concept of episteme in Plato’s philosophy. We start from the presupposition that the philosopher introduces new hypotheses during the period of the intermediate dialogues. Foundations from this evaluation appear in Meno, where Plato distinguishes episteme from doxa and introduces the theory of anamnesis. In Phaedo, Thaetetus and Republic, Plato systematizes his ideas and develops important concepts, as aisthesis. Our intention is to find out how the philosopher treats and relates those concepts within the dialogues that we are going to analyze and, above all, we want to answer to the question: maintains Plato a conceptual unity regarding the meaning of episteme or changes his views as he evolves to a more mature conception in the aforementioned dialogues?